Industry 4.0 - On-line Sinter Properties Control And Mining Tailings Preparation - Eduardo de Oliveira Cabral; Elen Mancini Santi Paulettor; Vinicius Calheiros (Associacao Brasileira de Metalurgia, Materiais e Mineracao, 2019)
At this paper, Eirich will present its new tool for sinter analysis integrated to the sintering control system. For stabilization and optimal, continuous control of the sintering process, QualiMaster MT1, a device was developed which guarantees fully automatic representative sampling and material analysis and thus a high and stable sintering quality. Mining tailings often has a considerable proportion of valuable substances. In addition to this work, we will also present our mixing technology that allows the economic recovery of these mining tailings.